TANGGUNG JAWAB NEGARA TERHADAP ANAK JALANAN PADA BIDANG PENDIDIKAN - Sofyan, Andi Muhammad; Tenripadang, Andi (LPPM IAIN Parepare, 2017)
The responsibility of protecting the right to education of street children that the responsibility of the government, the provincial government, the district/ city government, and the obligations of parents of guardians, parents, families, and communities and countries. The management of education shall be the responsibility of the government and shall be responsible for any loss incurred on the fautes personalles (ie the loss to the third party charged to the officer, the fautes the services of the third party) shall be borne by the agency and the responsibility of the facility. The responsibility for the protection of street children's right to education should be given responsibility to the state through the government, provincial government, district/ municipal government by involving the community and the institution whose management is regulated and adapted to the ideals of the country and the conditions of each community in the region